Avaliação de corrosão sob tensão e corrosão-fadiga do aço API 5L X70 em solução etanólica sintética - Santos, Elielson Alves dos (2022)
API X70 steel has been widely used in Brazil for the manufacture of ethanol transport pipelines, however, a recognized problem in carbon steel pipes exposed to ethanol is stress corrosion cracking (SCC) and, in addition, the pipelines are subject to fuel pressure fluctuations, causing concern in relation to fatigue. The objective of this research was to evaluate the SCC and corrosion-fatigue (CF) for X70 steel exposed to a circulating synthetic ethanol solution (CSES), with a view to the microstructure/environment interaction. Quench treatment in synthetic mineral oil was developed to modification of as-received microstructure. Mechanical tests were performed to analyze susceptibility to SCC, as well as cyclic loading tests to get fatigue crack growth rates (da/dN). Results on notched specimens with as-received microstructure (RA) and heat treated as-received microstructure (HTRA) revealed a strain reduction around 58% and 37%, respectively, after slow strain rate tests in CSES. Under constant load (CL), the RA microstructure steel appears no be sensitive to SCC at stress levels below the yield strength, however, under staggered constant load (SCL) the phenomenon was observed in both types of microstructure. The presence of corrosion product in the fracture surface initiation region for RA microstructure suggests crack closure, causing alterations in the initial portion of the da/dN-ΔK curves, shifting ΔKlim to higher values. Changes in crack growth rates in the Paris-Erdogan linear region for RA microstructure, at low ΔK levels at 0.25 Hz, were identified due to SCC, as well as some crack acceleration due to corrosion-fatigue. The interaction between HTRA microstructure and ethanol solution revealed lower da/dN rates when compared to rates obtained by contact of the solution with the RA microstructure.